(untitled) (Journal of Asian Geography, 2026)
This preliminary study examines residents’ awareness of river stewardship and their engagement with technology in Kampung Paya Rawa, a rural community in Mukim Temin, Kedah, Malaysia. Conducted under the Celik Digital, Cakna Kebersihan campaign, the study assesses community knowledge, moral values, sense of responsibility, and technology-related awareness in relation to river conservation. Data were collected through face-to-face surveys with 51 residents over two days in April 2025, enabling direct engagement and a contextual understanding of local perspectives. A descriptive analysis was undertaken to evaluate awareness across the four dimensions. The findings indicate that the community demonstrates a moderate level of awareness in all areas assessed. Residents exhibit a strong emotional and cultural attachment to the river and generally recognise its importance for daily life and environmental sustainability. However, their knowledge of river management, flood risks, and responsible practices remains limited, indicating a gap between general awareness and informed action. Although there is a clear willingness to participate in river care activities, actual engagement appears limited. The study also identifies high smartphone ownership among residents, suggesting considerable potential for integrating digital tools to support environmental education, early warning systems, and community mobilisation, despite only moderate levels of technology-related knowledge. Overall, the findings suggest that combining environmental education with accessible digital initiatives could enhance river stewardship practices in rural communities. This study provides baseline insights to inform future interventions, community-based programmes, and policy-oriented efforts aimed at strengthening sustainable river management through the integration of awareness and technology.